2016
DOI: 10.1007/s10995-016-2008-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Chinese-Translated Version of a Pregnancy Physical Activity Questionnaire

Abstract: Objectives The objectives of the present study were to translate the English version of the Pregnancy Physical Activity Questionnaire into Chinese (PPAQ-C) and to determine its reliability and validity for use by pregnant Chinese women. Methods The study included 224 pregnant women during their first, second, or third trimesters of pregnancy who completed the PPAQ-C on their first visit and wore a uniaxial accelerometer (Lifecorder; Suzuken Co. Ltd) for 7 days. One week after the first visit, we collected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 24 publications
6
51
0
Order By: Relevance
“…In this research, vigorous levels of PA, mostly conducted in sports or exercise context, were not observed across the trimesters of pregnancy. These results join those obtained in the Chinese study, where few pregnant women reported engaging in high intensity/vigorous activities [29]. Similar results were obtained by Yi-Li Ko et al in a cohort of 150 pregnant women in Taiwan [33].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…In this research, vigorous levels of PA, mostly conducted in sports or exercise context, were not observed across the trimesters of pregnancy. These results join those obtained in the Chinese study, where few pregnant women reported engaging in high intensity/vigorous activities [29]. Similar results were obtained by Yi-Li Ko et al in a cohort of 150 pregnant women in Taiwan [33].…”
Section: Plos Onesupporting
confidence: 90%
“…Our sample size, age, gestational trimesters, and pre-gestational BMI were similar to the study of Xiang Mi et al, which used the Chinese version of PPAQ, among 182 pregnant women, having mostly an initial BMI in the normal category [29].…”
Section: Plos Onementioning
confidence: 70%
“…After reading the full-texts, ten articles were excluded because of the absence of measurement properties ( n = 5) [ 29 33 ] or using a diary/record ( n = 3) [ 34 36 ] or an interview ( n = 2) [ 37 , 38 ]. Finally, 17 articles [ 39 55 ] on 11 different PA questionnaires (17 versions) [ 39 , 44 , 56 63 ] were included (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In most studies, an accelerometer was used as a comparison measure. Eight studies [ 42 46 , 49 , 51 , 55 ] assessed the measurement properties of the Pregnancy Physical Activity Questionnaire (PPAQ) [ 44 ] or adaptations of this questionnaire (e.g., Japanese version). Another study [ 48 ] evaluated the long form of the IPAQ, whereas two studies (of reliability and construct validity), reported in one article [ 52 ], evaluated the short form of the IPAQ (IPAQ-SF).…”
Section: Resultsmentioning
confidence: 99%
“…PA during pregnancy was assessed by using the Chinese version of the Pregnancy Physical Activity Questionnaire, which is a semiquantitative questionnaire validated for use during pregnancy (ICC = 0.77, r = 0.35) [18,19]. The original Pregnancy Physical Activity Questionnaire assesses the duration, frequency, and intensity of different types of PA during pregnancy [19].…”
Section: Assessment Of Pamentioning
confidence: 99%